Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Bùi Đặng Dũng (Số: 12282/BCT-KH) - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Bùi Đặng Dũng (Số: 12282/BCT-KH) ngày 20/12/2016